Excellent performance of mesoporous Co3O4/MnO2 nanoparticles in heterogeneous activation of peroxymonosulfate for phenol degradation in aqueous solutions - Liang, Hanwen; Sun, Hongqi; Patel, A.; Shukla, P.; Zhu, Z.; Wang, Shaobin (elsevier, 2012)
Mesoporous α-MnO2 and its supported Co3O4 nanoparticles were synthesized, characterized and tested in heterogeneous activation of peroxymonosulfate (PMS) for phenol degradation in aqueous solution. α-MnO2 supported Co3O4 presented as nanorod particles and showed H2 redox reduction at low temperature. Bulk α-MnO2 and Co3O4 could activate peroxymonosulfate to generate sulfate radicals for phenol degradation but at low activity. Co3O4/MnO2 nanoparticles exhibited much high activity in peroxymonosulfate activation for phenol degradation with 100% conversion in 20 min and 3 wt% is the optimum Co loading. Phenol degradation followed a first order kinetics. Stability tests also showed that Co3O4/MnO2 presented stable performance in phenol degradation in several runs.